Roomies ebook - Lauren, Christina (2017)
From subway to Broadway to happily ever after. Modern love in all its thrill, hilarity, and uncertainty has never been so compulsively readable as in New York Times bestselling author Christina Lauren's Roomies . Marriages of convenience are so ...inconvenient. For months Holland Bakker has invented excuses to descend into the subway station near her apartment, drawn to the captivating music performed by her street musician crush. Lacking the nerve to actually talk to the gorgeous stranger, fate steps in one night in the form of a drunken attacker. Calvin Mcloughlin rescues her, but quickly disappears when the police start asking questions. Using the only resource she has to pay the brilliant musician back, Holland gets Calvin an audition with her uncle, Broadway's hottest musical director. When the tryout goes better than even Holland could have imagined, Calvin is set for a great entry into Broadway—until his reason for disappearing earlier becomes clear: he's in the country illegally, his student visa having expired years ago. Seeing that her uncle needs Calvin as much as Calvin needs him, a wild idea takes hold of her. Impulsively, she marries the Irishman, her infatuation a secret only to him. As their relationship evolves and Calvin becomes the darling of Broadway—in the middle of the theatrics and the acting-not-acting—will Holland and Calvin to realize that they both stopped pretending a long time ago?